Assessment of University Gynaecology Clinics Based on Quality Reports - Solomayer, E. F.; Rody, A.; Wallwiener, D.; Beckmann, M. W. (Geburtshilfe und Frauenheilkunde, 2013)
Introduction: Quality reporting was initially implemented to offer a better means of assessing hospitals and to provide patients with information to help them when choosing their hospital. Quality reports are published every 2 years and include parameters describing the hospitalʼs structure and general infrastructure together with specific data on individual specialised departments or clinics. Method: This study investigated the 2010 quality reports of German university hospitals published online, focussing on the following data: number of inpatients treated by the hospital, focus of care provided by the unit/department, range of medical services and care provided by the unit/department, non-medical services provided by the unit/department, number of cases treated in the unit/department, ICD diagnoses, OPS procedures, number of outpatient procedures, day surgeries as defined by Section 115b SGB V, presence of an accident insurance consultant and number of staff employed. Results: University gynaecology clinics (UGCs) treat 10 % (range: 6–17 %) of all inpatients of their respective university hospital. There were no important differences in infrastructure between clinics. All UGCs offered full medical care and were specialist clinics for gynaecology (surgery, breast centres, genital cancer, urogynaecology, endoscopy), obstetrics (prenatal diagnostics, high-risk obstetrics); many were also specialist clinics for endocrinology and reproductive medicine. On average, each clinic employs 32 physicians (range: 16–78). Half of them (30–77 %) are specialists. Around 171 (117–289) inpatients are treated on average per physician. The most common ICD coded treatments were deliveries and treatment of infants. Gynaecological diagnoses are underrepresented. Summary: UGCs treat 10 % of all inpatients treated in university hospitals, making them important ports of entry for their respective university hospital. Around half of the physicians are specialists. Quality reports offer little information on the differences in competencies or medical specialties. The statutory quality reports are not useful for patients and referring physicians when choosing a clinic.
Keywords: gynaecology; obstetrics; reproductive medicine